Dental arch form and interdental widths evaluation in adult Caucasian patients with obstructive sleep apnea syndrome. Issue 2 (4th March 2023) - Irlandese, Giuliano; De Stefani, Alberto; Mezzofranco, Luca; Milano, Francesca; Di Giosia, Massimiliano; Bruno, Giovanni; Gracco, Antonio
ABSTRACT: Objective: To evaluate the hypothesis that dental arch form and inter-canine, inter-premolar, and inter-molar widths differ between OSAS patients and non-snoring, non-apneic controls. Methods: Dental digital models from 64 OSAS patients and 64 control subjects were used to obtain dental arch forms and to compare them between the two groups. Arch forms were extracted from the lower arch models using a professional graphics program and an orthodontic digital template. Through an orthodontic software, inter-molar, inter-premolar, and inter-canine widths were measured for both upper and lower arches. Results: The dental arch forms distribution differed between OSAS patients and controls. OSAS patients had reduced inter-canine, inter-premolar, and inter-molar widths for both arches compared to controls. Discussion: These results suggest that OSAS patients have narrower and more tapered arches than controls. Dental arch morphology and interdental widths differ between OSAS and control groups, supporting the hypothesis that they are an etiological factor.